2010
DOI: 10.1097/mjt.0b013e3181a4695f
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Suppression: A Side Effect of Ciprofloxacin Therapy

Abstract: Ciprofloxacin is a commonly used antibiotic for gastrointestinal and genitourinary tract infections with a considerably good safety profile. However, occasionally it may cause life-threatening complications. Two case reports of bone marrow depression and 1 case of thrombocytopenia due to ciprofloxacin therapy have been reported in literature. We report a case of bone marrow depression due to ciprofloxacin therapy for urinary tract infection in an otherwise healthy woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…As the knowledge regarding timing of ciprofloxacin- and piperacillin/tazobactam-induced thrombocytopenia is based on case reports, it is not possible to reliable estimate the time course of thrombocytopenia from that review. However, interestingly, several other published reports regarding antimicrobial-induced thrombocytopenia describes decreasing platelet count and development of thrombocytopenia within 4 days after exposure to ciprofloxacin [15,18-20] and piperacillin/tazobactam [21-23] consistent with our findings. The great diversity in timing is most likely explained by varying mechanisms causing drug-induced thrombocytopenia [7,10],including that prior exposure may have already sensitised some patients leading to more rapid effects upon reexposure [13].…”
Section: Discussionsupporting
confidence: 92%
“…As the knowledge regarding timing of ciprofloxacin- and piperacillin/tazobactam-induced thrombocytopenia is based on case reports, it is not possible to reliable estimate the time course of thrombocytopenia from that review. However, interestingly, several other published reports regarding antimicrobial-induced thrombocytopenia describes decreasing platelet count and development of thrombocytopenia within 4 days after exposure to ciprofloxacin [15,18-20] and piperacillin/tazobactam [21-23] consistent with our findings. The great diversity in timing is most likely explained by varying mechanisms causing drug-induced thrombocytopenia [7,10],including that prior exposure may have already sensitised some patients leading to more rapid effects upon reexposure [13].…”
Section: Discussionsupporting
confidence: 92%
“…This patient made a successful recovery after the ciprofloxacin was stopped. 2 In conclusion, our case highlights a very rare side effect of ciprofloxacin, and hence, health care providers should watch out for this potential adverse effect when prescribing ciprofloxacin.…”
mentioning
confidence: 69%
“…Tuccori et al [4] observed abdominal pain, hepatitis, thrombocytopenia, and hemolysis in a 30-year-old patient after ciprofloxacin treatment for urinary tract infection. In addition to this, Chaudhry et al [5] observed that thrombocytopenia occurred as a result of ciprofloxacin treatment for urinary tract infection.…”
mentioning
confidence: 94%